Šavrinke - preprodajalke med osrednjo Istro in obalnimi mesti ter nosilke simbolnih identifikacij - Ledinek Lozej, Špela (Dve domovini, 2014)
The paper presents the sociohistorical conditions, trade routes and everyday life of migrant women traders from the north-eastern Istrian countryside. In the first half of the 20th century they traded in central Istria, where they gathered eggs, and paid for them with consumer goods, e. g. thread, soap, paraffin, salt, kerchiefs and handkerchiefs and other goods, and sold them in Trieste. The egg-selling centres, the main weekly trade routes and the conditions under which the women involved in this activity worked are listed and discussed. In the conclusion the role of the migrant women traders (known as Šavrinkas in central Istria) in the preservation of the original ethnic label Šavrini and in the processes of the "šavrinization" of the northern Istrian countryside is outlined.
Keywords: Delovne migracije; ethnology; Etnologija; human migration; Istra; Istria; jajčarice; labour migration; Migracije; Način življenja; Šavrinke; Trieste; Trst